If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -4x = -5 + 8x Solving 3 + -4x = -5 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 3 + -4x + -8x = -5 + 8x + -8x Combine like terms: -4x + -8x = -12x 3 + -12x = -5 + 8x + -8x Combine like terms: 8x + -8x = 0 3 + -12x = -5 + 0 3 + -12x = -5 Add '-3' to each side of the equation. 3 + -3 + -12x = -5 + -3 Combine like terms: 3 + -3 = 0 0 + -12x = -5 + -3 -12x = -5 + -3 Combine like terms: -5 + -3 = -8 -12x = -8 Divide each side by '-12'. x = 0.6666666667 Simplifying x = 0.6666666667
| -5(t-8)-(t+7)=7 | | 6t=3t+12 | | f=1.5w(2k+b)+10 | | 10x-(20-40x-60)=5x-3(4x-2) | | 2x+16x+30=0 | | -3x+y=0 | | 2a+3b-4c-2a= | | 3(w-6)=-18 | | -6x^2-17x+3=0 | | 3x-(4x-2)=5x-(5-4x) | | -7x-9=33 | | 16x-8=48 | | -6x+y=2 | | 6x-20(2x-4)=6-20+4x | | 0=-2x^2+4x-4 | | y=-2x^2+4x-4 | | 1+5x-x=-7 | | 21=-7Y | | 2n^2+5n-9=0 | | 6d+14=-7-d | | -3x-6x+45=0 | | -7x-6x=13 | | -3x*-6x+45=0 | | 5x-(50-4)=10x-40 | | x^2=19+5x | | 3x=91 | | -3x+5x=-8 | | 8(c-3)+3=2+c-23 | | 6X-138= | | 7(2+k)=28 | | 8a-6a=-12 | | -8=12-4x |